Localization analysis in softening RC frame structures. - Khaloo, Ali R.
This paper discusses the sensitivity of softening reinforced concrete frame structures to the changes in input ground motion and investigates the possibility of localizations for this type of structure in static and dynamic analysis. A finite element model is used in which the sections resisting force are calculated using a proposed differential hysteretic model. This model is especially developed for modelling softening behaviour under cyclic loadin. To obtain parameters of the differential model the moment curvature of each section is evaluated using a microplane constitutive law for concrete and bi linear elasto plastic law for reinforcements. The capability of the procedure is verified by comparing results with available experimental data at element level, which shows good accuracy of the procedure. The effect of possible changes in ground motion is assessed using a non stationary Kanai Tajimi process. This process is used to generate ground motions with approximately the same amplitude and frequency content evolution as those of base ground motion. The possibility of localization in static and dynamic loading is investigated using two structures. A measure for the possibility of localization in code designed structures is obtained. This study indicates that localization may occur in ordinary moment resisting structures located in high seismic zones. Localization may result in substantial drift in global response and instability due to P effect. Also, it is shown that the structure becomes very sensitive to the input ground motion. It is concluded that allowance by some design codes of the use of ordinary moment resisting frames in regions with high seismicity should be revised or improvements should be made in the detailing requirements at critical sections of these structures.
Keywords: Differential hysteretic model; Flexibility based finite element; Localization; Microplane model; Softening; Synthetic ground motion